6-Mercaptopurine/Azathioprine remains an important contributor in managing Crohn's disease. (1st August 2014) - Korelitz, Burton I.; Present, Daniel H.
Abstract: Two large studies concluded that AZA started early after diagnosis of Crohn's disease have no late maintenance value. This is contrary to previous studies on 6MP for Crohn's disease and could lead to negating the value of two of the few drugs that have been proven successful. We here outline the many reasons why 6MP remains a valuable drug in the treatment of Crohn's disease.